(untitled) (Palíndromo, 2026)
This work seeks to situate the sublime within the poetics and aesthetic experiences of post-digital art, a term that emerged in the 2010s to describe practices driven by the ubiquitous use of computational encoding and its hybridization with analog media. Specifically, we examine the reconfigurations and shifts within this context under the impact of the prolific production and circulation of creative content across digital networks, fueled by the adoption of generative AI. To do so, we draw upon both modern and postmodern definitions of the sublime, discussing these concepts in light of the aesthetic theories of informational ecology and formativity. The understanding arising from the context of network saturation with creative and generative products proves to be of paramount importance in considering the possible manifestations of the sublime today, in works by artists such as Tyler Hobbs and Bianca Tse.